1969
DOI: 10.1039/df9694700126
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer spectra, structure, and bonding in iron carbonyl derivatives

Abstract: The Mossbauer spectra of the mono-, di-, tri-, and tetra-nuclear iron carbonyl anions and carbonyl hydride anions are reported and compared with the known spectra of the neutral binary carbonyls.Increase in anionic charge in the sequence 0, -1, -2 results in progressively lower values of chemical isomer shift 6 for each series. In addition, there is a systematic increase in 6 as the co-ordination number of iron increases from 4 to 7. These trends are interpreted in terms of changes in the bonding in these comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
36
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 1 publication
6
36
0
Order By: Relevance
“…An interesting result is that the magnitude of this effect seems to be rather independent of the computational method applied. Structural effects can be obtained by comparing the different EFGs at the B3LYP level in different geometries ͑in a.u.͒: PAW geometry 26 we obtain a final NQM of Q ϭϩ0.12 b. This would support the value derived by Su and Coppens.…”
Section: A Fe"co…supporting
confidence: 81%
“…An interesting result is that the magnitude of this effect seems to be rather independent of the computational method applied. Structural effects can be obtained by comparing the different EFGs at the B3LYP level in different geometries ͑in a.u.͒: PAW geometry 26 we obtain a final NQM of Q ϭϩ0.12 b. This would support the value derived by Su and Coppens.…”
Section: A Fe"co…supporting
confidence: 81%
“…In this case the Mössbauer spectrum is expected to show two different types of resonance signals with intensity ratio of 2:1. The measured Mössbauer spectrum of Fe 3 (CO) 12 [35] (right) shows two types of resonance signals, A and B, and confirms that the structure with two types of iron positions is the correct one. and rhombically distorted, which leads to nonzero EFG and the observed quadrupole splitting in the Mössbauer spectrum.…”
Section: Molecular Symmetry -Information From Quadrupole Splittingsupporting
confidence: 57%
“…In this case the Mössbauer spectrum is expected to show two different types of resonance signals with an area ratio of 2:1. A Mössbauer effect study performed by Greatrex and Greenwood in 1969 [35] indeed showed two types of resonance signals, a quadrupole doublet A and a singlet B with an area ratio of 2:1 confirming the presence of two types of iron positions in Fe 3 (CO) 12 (Figure 15).…”
Section: Molecular Symmetry -Information From Quadrupole Splittingmentioning
confidence: 84%
“…Curiously Zhang et al cite the same experimental paper for their value of À0.18 mm s À1 , as do Kurian and Filatov 25 who report À0.140 mm s À1 . More recent experimental isomer shifts for Fe(CO) 5 are reported by Greatrex and Greenwood75 and Kuhn et al76 who report +0.17 mm s À1 (77 K) and +0.18 mm s À1 (113 K), respectively, both using hydrated sodium nitroprusside at room temperature as reference, which translates into À0.088 mm s À1 and À0.078 mm s À1 relative to a-Fe foil. Finally, for completeness, a Mo ¨ssbauer isomer shift of À0.174 mm s À1 is reported by De Paoli et al77 at 4.2 K for Fe(CO) 5…”
mentioning
confidence: 84%